Ellipsoid Zone and External Limiting Membrane-Related Parameters on Spectral Domain-Optical Coherence Tomography and Their Relationships With Visual Prognosis After Successful Macular Hole Surgery - Jiarui Yang (Frontiers Media S.A., 2021)
Purpose: To compare structural diameters of the ellipsoid zone (EZ) and external limiting membrane (ELM) bands on spectral domain-optical coherence tomography (SD-OCT) images between vision-improved (group A) and vision-unimproved (group B) patients, and investigate the connection between these parameters and visual prognosis.Materials and Methods: Forty-five eyes of 43 patients with idiopathic full-thickness macular hole closed after vitrectomy were retrospectively reviewed. Best-corrected visual acuity (BCVA) and SD-OCT were conducted preoperatively and at 1 week, 1 month and 6 months postoperatively. Structural and functional parameters were then measured using ImageJ software.Results: Among structural and functional parameters, the relative reflectivity of EZ and the ratio of continuous ELM and EZ in group A were significantly higher than in group B from the 1-month postoperative visit. At the 6-month follow-up, the diameter of EZ disruption in group A was significantly smaller than in group B, and the relative reflectivity of ELM/EZ was significantly higher than group B. At 6-months, BCVA was statistically significantly correlated with baseline BCVA, basal diameter (BD), macular hole index (MHI), and diameter of ELM/EZ disruption. Change in BCVA from baseline was found to be significantly correlated with axial length and diameter hole index (DHI).Conclusions: Postoperative BCVA outcome was significantly correlated with integrity, thickness and reflectivity of the EZ band. Patients with smaller diameter of EZ disruption and higher reflectivity of EZ band tended to have better visual outcomes. Given that the EZ band reflects the recovery of mitochondria in photoreceptors, it is a promising parameter for their functional evaluation.